2019
DOI: 10.1177/1440783319888283
|View full text |Cite
|
Sign up to set email alerts
|

Thrown into the world: The shift between pavlova and pasta in the ethnic identity of Australians originating from Italy

Abstract: Forty-one years on from Huber’s study exploring the assimilation of Italian-Australians, an increasing trend towards ethnic revival can be observed among the third generation of immigrants. Drawing on a case study of a family originating from Calabria in the 1950s and now living in Adelaide, South Australia, I find a widespread intergenerational identification of ethnicity as ‘being Italian’, which has different meanings across the three generations, depending on the individual’s phenomenological perception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…More recent scholarship on migration has suggested that migrants’ ethnic identity is fluid and ‘in-between’ (Ahmed, 2005; Ip, 2008; Marino, 2019; Ng, 2016; Van Zevern, 1995; Vasquez, 2010). Transnationalism literature concurs that a borderless identity and sense of belonging among migrants and migrant children is not only common but also necessary because of the multiple options and unlimited mobility offered by a post-territorial and globalized socio-economic and socio-cultural setting.…”
Section: Theoretical Background: From In-between To Plural Ethnicitiesmentioning
confidence: 99%
“…More recent scholarship on migration has suggested that migrants’ ethnic identity is fluid and ‘in-between’ (Ahmed, 2005; Ip, 2008; Marino, 2019; Ng, 2016; Van Zevern, 1995; Vasquez, 2010). Transnationalism literature concurs that a borderless identity and sense of belonging among migrants and migrant children is not only common but also necessary because of the multiple options and unlimited mobility offered by a post-territorial and globalized socio-economic and socio-cultural setting.…”
Section: Theoretical Background: From In-between To Plural Ethnicitiesmentioning
confidence: 99%
“…It is worth reiterating here how for cultural norms to be exploited, these cultural norms must be indeed well ingrained in the community. Obligations, expectations, and behavioral dispositions across families in Calabrian and Italian communities are inherited and maintained (albeit in an integrated or hybrid Australian way) as a peculiar way of being and doing (Marino, 2019c;Marino, 2020a). Ethnic solidarity is part of the identity of Calabrians and Italians in Australia as abroad (Harney, 2006) and, as already argued elsewhere (Sergi, 2021) can become a reason why certain individuals might feel obliged to-and be exploited into-support other "co-regionals/co-nationals" and become involved into complex webs of criminal or semicriminal activities.…”
Section: Conceptual Hiccupsmentioning
confidence: 99%
“…Even more so, we could look at the ways in which newer generations of Australian-born of Calabrian origins perceived their Calabrian background in Australia because this might have a direct impact on the reasons why 'ndrangheta behaviors are not only inherited by family blood (as it's the case in Calabria/Italy) by might also be chosen-to a certain extent-by younger generations. Indeed, if it is true that idolization, romanticization, and ethnical revival of Calabrian roots is not uncommon among younger generations (Marino, 2019c), then these are all strong elements to explain why among these Calabrian roots also 'ndrangheta roots persist.…”
Section: Final Considerationsmentioning
confidence: 99%